Identification and analysis of 5‐enolpyruvylshikimate‐3‐phosphate synthase (EPSPS) gene from glyphosate‐resistant Ochrobactrum intermedium Sq20. Issue 5 (12th August 2017) - Firdous, Sadiqa; Iqbal, Samina; Anwar, Samina; Jabeen, Hina
Abstract: BACKGROUND: Glyphosate is a herbicide that acts by inhibition of the enzyme, 5‐enolpyruvylshikimate‐3‐phosphate synthase (EPSPS), involved in the catalysis of an essential step in the biosynthesis of aromatic amino acids. The objective of this study was the isolation of glyphosate‐resistant bacterial strains and subsequent characterization of the gene(s) encoding glyphosate resistance in these isolates. Using an enrichment culture technique, a glyphosate‐resistant bacterium, Ochrobactrum intermedium Sq20 was isolated from glyphosate‐contaminated indigenous soil and characterized. RESULTS: An open reading frame (ORF) comprising of 1353 bp potentially encoding aroA O. intermedium Sq20 was amplified from O. intermedium Sq20. It showed 97% homology with aroA genes from other Ochrobactrum spp. Physicochemical characterization revealed that aroA O. intermedium Sq20 encodes a polypeptide of 450 amino acids with a calculated molecular mass of 48.9782 kDa and an isoelectric point of 5.21. Secondary structure prediction of AroA O. intermedium Sq20 demonstrated a high percentage of random coils and α helices. Methodical optimization and validation of the protein structure helped to build a reliable protein model indicating the presence of 91.8% amino acid residues in most favoured regions. In addition, strain Sq20 was found to be capable of complete degradation of glyphosate at 500 mg L –1 initial concentration as the sole carbon and energy source within 4 days. CONCLUSION: A glyphosate‐resistant bacterial strain O. intermedium Sq20 was discovered. Sequence analysis and structure modelling demonstrated that AroA O. intermedium Sq20 closely resembles class II EPSPS and possesses high glyphosate resistance. This provides a good foundation for functional analysis of experimentally derived crystal structures. The cloning and characterization of AroA O. intermedium Sq20 will further help in understanding its role at the molecular level and its potential use in the production of glyphosate‐resistant transgenic crops. © 2017 Society of Chemical Industry Abstract : A glyphosate‐resistant bacterial strain O. intermedium Sq20 was isolated. Sequence analysis and structure modelling demonstrated that AroA O.intermedium Sq20 closely resembles class II EPSPS which provides foundation for its functional analysis.